KAJIAN ON JOB TRAINING BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH (BAPPEDA) PROVINSI JAWA TENGAH - Siti Kris Agustia Marselia (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
The On The Job Training (OJT) activity is an activity that is included in the curriculum of all Study Programs at the Indonesian Tourism Economics College (STIEPARI) Semarang and must be carried out by students who are currently studying in semester VI. On The Job Training (OJT) is an activity to go directly to the field and apply the things obtained from theory and compared with practice in the field. From semester I to semester V, students of the Indonesian Tourism Economics College (STIEPARI) Semarang have been equipped with various practical skills and solving problems that exist in each study program so as to make it easier for students to practice in their respective fields.